Rancang Bangun Sistem Informasi Penjualan menggunakan CMS Wordpress untuk Meningkatkan Efisiensi UMKM dengan Biaya Terjangkau - B.T. Sutrisno. SP.; Hendra Hendra; Kuindra Iriyanta; Aji Awang Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of information technology has become a crucial need for Micro, Small, and Medium Enterprises (UMKM) in the digital era, despite frequent constraints in funding and technical resources. This study aims to explore the use of WordPress CMS as an affordable and easily implementable sales information system solution for UMKM. WordPress was chosen due to its flexibility in managing various products, including food and manufactured goods, at a lower cost compared to custom system development. The research method includes analyzing WordPress implementation for UMKM, identifying its strengths and weaknesses, and comparing costs with custom-built systems. The results indicate that WordPress can be an effective and economical solution for UMKM, offering various plugins that can be tailored to business needs without requiring deep technical expertise. This study provides practical guidance for UMKM in utilizing WordPress to enhance online sales with minimal budgets, while also contributing to the literature on the application of low-cost technology to support MSME growth in Indonesia.